Cystophora cristata - W. Christopher Wozencraft (Smithsonian Institution Press, 1993)
Cystophora cristata (Erxleben, 1777). Syst. Regni Anim., 1:590. TYPE LOCALITY: "Habitat in Groenlandia australiori et Newfoundland". [S Greenland and Newfoundland]. DISTRIBUTION: N Atlantic and Arctic oceans, from Newfoundland (Canada) to S Greenland, Svalbard and Novaya Zemlya (Russia); occasionally south to Portugal and Florida (USA). SYNONYMS: borealis Nilsson, 1820; dimidiata Riippell, 1842. COMMENTS: Reviewed by Kovacs and Lavigne (1986, Mammalian Species, 258). Published as part of W. Christopher Wozencraft, 1993, Order Carnivora, pp. 279-348 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 329, DOI: 10.5281/zenodo.7359191